Using a hybrid adsorption-membrane filtration system to produce biologically stable drinking water - Omalanga, Landry Sendango (University of the Witwatersrand, Johannesburg, 2024)
The purpose of water treatment is to produce clean and safe drinking water, for consumers. Water quality, both during treatment and distribution, is greatly affected by the presence of natural organic matter (NOM). The presence of NOM affects the effectiveness of water treatment processes and sometimes increases the cost of water treatment and leads to operational problems. Furthermore, the presence of biodegradable organic matter (BOM), which is a fraction of NOM, can degrade water quality during distribution resulting in the loss of biological stability. The excessive presence of BOM can be addressed using advanced water treatment processes or by relying on systems which combine multiple water treatment processes to increase treatment efficiency. The main aim of this study was to evaluate the effectiveness of a hybrid adsorption- membrane filtration system in lowering the bacterial regrowth potential in water. Ready-made multi-walled carbon nanotubes (MWCNTs) were used as adsorbents in this study. MWCNTs were chosen because they exhibit high adsorption properties mainly because of their fibrous shape and external surface accessibility. MWCNTs have hydrophobic characteristics and a propensity to aggregate due to the presence of electrostatic interactions among them, therefore, functionalization of MWCNTs was required to improve their dispersion in the organic and inorganic solvents. A non-covalent functionalization process was employed using cetyltrimethylammonium bromide (CTAB) as a cationic surfactant to ameliorate the stability and dispersibility of MWCNTs in aqueous solution. The non-covalent functionalization was preferred to sustain the functionalities needed for BOM capture enhancement and environmental safety. Polysulfone (PSF) membranes were produced by phase inversion method using N, N- dimethylformamide as solvent for the removal of BOM from water. The phase inversion method was chosen in this study due to its simple processing, flexible production scales, and low cost. The MWCNTs and PSF membranes were characterized using microscopy techniques such as transmission electron microscopy (TEM), scanning electron microscopy (SEM), X ray diffraction (XRD), Raman spectroscopy, tensile strength test, and the hydrophilicity (contact angle) test. These techniques were selected because they enable the evaluation of the morphology, composition, physical characteristics, and dynamic behavior of nanostructured materials. iv Batch adsorption experiments were employed to investigate the adsorption properties of functionalized MWCNTs for BOM removal. Four different concentrations of functionalized MWCNTs were tested to determine the ideal conditions for the adsorption of two forms of BOM; assimilable organic carbon (AOC) and biodegradable dissolved organic carbon (BDOC), from water. The concentrations of functionalized MWCNTs used were 4, 8, 12, and 16 mg in 100 mL of BOM solution. Furthermore, the cross-flow filtration mode, also known as tangential flow filtration, was used to separate the remaining BOM in water by passing water along the surface of the NF membrane using pressure difference. Cross-flow filtration was chosen because it removes the buildup from the surface of the membrane and provides the benefit of an improved membrane lifespan by helping to prevent irreversible fouling. A mathematical model of membrane filtration process in continuous system was also developed to better understand the correlations between the different variables of the membrane filtration process such as the inlet (feed) concentration (Cin) and flow rate (Qin), and the outlet (retentate) concentration (Cout) and flow rate (Qout), and the permeate concentration Cp. Results obtained after the functionalization process of MWCNTs showed an improvement in their stability and dispersibility in aqueous solution. The characterization of both MWCNTs and PSF membranes showed some interesting features. For example, morphological and structural studies show that MWCNTs possess fibrous shapes with a high aspect ratio, and a hollow structure with an inner diameter. The finger-like structures found on the surfaces of PSF membranes play a crucial role in their adsorption capabilities. These structures, which vary in pore size, contribute to the overall capacity of the membranes to absorb BOM from water. During adsorption experiments, it was observed that the removal of BOM from water increased with an increase in the adsorbent (functionalized MWCNTs) concentration. This is likely due to high concentration gradient which acts as a driving force to overcome resistances to mass transfer of dye ions between the aqueous phase and the solid phase. However, the maximum removal of both AOC and BDOC was recorded at a concentration of functionalized MWCNTs of 12 mg, at a contact time of 4 hours and at an agitation speed of 180 rpm. The PSF membrane produced by phase inversion method demonstrated the highest flux of 0.0091 ml/cm2.min at room temperature (25°C) and after a filtration time of 90 minutes. The selectivity and permeate flux were increased with forward flushing and backwashing processes of the PSF membranes because it flushes out accumulated debris and particles on the surface and inside the pores of the membranes. After using the hybrid adsorption-membrane v filtration system, BDOC concentrations dropped to an average of 65% of the initial raw water BDOC and the AOC concentrations dropped to approximately 80% of the initial raw water AOC. Outputs from the mathematical model demonstrated that the change in initial conditions (Cin and Qin) is responsible for the transient response (changes from one steady state to another) in these membranes. The adsorption and membrane nanofiltration hybrid system adopted in this study, effectively removed both AOC and BDOC from water, and can therefore be used to produce biologically stable drinking water. The outcome of this study could be the application of the combination of BOM targeting strategies and residual disinfection to better control bacterial regrowth in drinking water distribution systems (DWDSs). This in turn could help water utilities with meeting distribution systems, water quality guidelines, and protect public health
A research report submitted in fulfillment of the requirements for the Doctor of Philosophy, In the Faculty of Engineering and the Built Environment , School of Civil and Environmental Engineering, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Drinking water; natural organic matter (NOM); carbon nanotubes (CNTs); functionalization process; adsorption process; membrane filtration process; hybrid system; SDG-3: Good health and well-being